2010
DOI: 10.1016/j.measurement.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Diesel engine fuel injection monitoring using acoustic measurements and independent component analysis

Abstract: Air-borne acoustic based condition monitoring is a promising technique because of its intrusive nature and the rich information contained within the acoustic signals including all sources. However, the back ground noise contamination, interferences and the number of Internal Combustion Engine ICE vibro-acoustic sources preclude the extraction of condition information using this technique. Therefore, lower energy events; such as fuel injection, are buried within higher energy events and/or corrupted by backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(58 citation statements)
references
References 17 publications
0
57
0
1
Order By: Relevance
“…In particular, the valve events from air intake exhaust and fuel injections can cause strong impacts. Hence, a number of acoustic emission based studies have been carried out to detect the faults of valve opening and closing impacts [4] [12] and needle impacts of injection [13] [14].…”
Section: Acoustic Emission Generation Of Piston Assemblymentioning
confidence: 99%
“…In particular, the valve events from air intake exhaust and fuel injections can cause strong impacts. Hence, a number of acoustic emission based studies have been carried out to detect the faults of valve opening and closing impacts [4] [12] and needle impacts of injection [13] [14].…”
Section: Acoustic Emission Generation Of Piston Assemblymentioning
confidence: 99%
“…Therefore, the development of an automobile engine condition monitoring system capable of providing early warning about the engine's state of operation is needed. Both the vibration [1,2] and sound signals [3,4] have been widely used for fault diagnosis. Xian et al [2] used a wavelet packet transform (WPT) for feature extraction in their reported work; however, the authors were targeting a vibration frequency band less affected by environment noise compared to sound.…”
Section: Introductionmentioning
confidence: 99%
“…Papers [5][6][7][8][9] present the application of the measurements of combustion engine noise and vibration in the analysis of damage to the injection system. This type of research was also conducted by the authors of [10], which analysed various types of damage to fuel injectors as well as damage to one or two injectors.…”
Section: Introductionmentioning
confidence: 99%